Low awareness of HPV infection and willingness of HPV vaccination among Chinese male college students in the east of China - Ran, Hu; Chen, Yue; Gao, Jun; Guo, Hongxiong; Peng, Shanshan (Frontiers in Public Health, 2022)
Introduction Human Papillomavirus (HPV) vaccine has proven to play a major role in preventing sexually transmitted diseases and related cancers among both men and women. However, the coverage of HPV vaccination is still limited. Objective The study aims to evaluate the awareness of HPV and HPV vaccine, as well as the willingness to take HPV vaccine, especially factors influencing vaccination willingness among male college students. Methods We conducted a cross-section investigation among male college students from 6 colleges in Jiangsu, China. A structured questionnaire was used to investigate the subjects’ basic information, behavior habits, cognition of HPV vaccine and the intention of HPV vaccination. Multivariate analysis modes were used to analyze the influencing factors of vaccine awareness and willingness. Results We found that among 912 participants, only 24.34% of the participants had a “good knowledge” of HPV and HPV vaccine and 34.54% showed “positive attitude" to the HPV vaccine after obtaining the knowledge of HPV and its vaccine. Factors such as immune persistence, side effects, pricing strategy and participants' self-assessment of HPV infection were the main factors influencing HPV vaccination. Conclusion Strengthening the health education on HPV vaccination and finding appropriate ways to solve the problem of "vaccine hesitancy" will be effective to improve the coverage of HPV vaccine and prevent related diseases. In addition, the lifting of restrictions on HPV vaccination for men in China may also prove useful.